PENGARUH PENGUASAAN MATERI MATA KULIAH DASAR KEPENDIDIKAN (MKDK) DAN PRAKTIK PROGRAM PENGALAMAN LAPANGAN (PPL) TERHADAP KESIAPAN MENJADI GURU - Murtiningsih, Yanita Janti; -, Susilaningsih; -, Sohidin (Jupe-Jurnal Pendidikan Ekonomi, 2013)
ABSTRAKPenelitian ini bertujuan untuk mengetahui: 1) pengaruh penguasaan materi mata kuliah Belajar & Pembelajaran 2 terhadap kesiapan menjadi guru; 2) pengaruh penguasaan materi mata kuliah Evaluasi Pengajaran terhadap kesiapan menjadi guru; 3) pengaruh penguasaan praktik PPL terhadap kesiapan menjadi guru; dan (4) pengaruh penguasaan materi mata kuliah Belajar & Pembelajaran 2, Evaluasi Pengajaran dan praktik PPL secara bersama-sama terhadap kesiapan menjadi guru. Penelitian ini adalah penelitian kuantitatif korelasional dengan pendekatan kausal-komparatif yang bersifat ex-post facto. Populasi penelitian ini adalah semua mahasiswa Prodi Pendidikan Ekonomi BKK Pendidikan Akuntansi. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Teknik pengumpulan data menggunakan metode kuesioner dengan skala Likert. Uji validitas instrumen menggunakan rumus korelasi Pearson Product Moment (PPM) dan uji reliabilitas menggunakan Koefisien Alpha. Uji prasyarat analisis data menggunakan uji normalitas, uji linieritas, uji multikolinieritas, uji heteroskedastisitas dan uji autokorelasi. Pengujian hipotesis menggunakan uji regresi linier sederhana dan uji regresi linier ganda. Hasil penelitian menyimpulkan bahwa: 1) Terdapat pengaruh positif dan signifikan penguasaan materi mata kuliah Belajar & Pembelajaran 2 terhadap kesiapan menjadi guru; 2) Terdapat pengaruh positif tetapi tidak signifikan penguasaan materi mata kuliah Evaluasi Pengajaran terhadap kesiapan menjadi guru; (3) Terdapat pengaruh positif dan signifikan penguasaan praktik PPL terhadap kesiapan menjadi guru; dan 4) Terdapat pengaruh positif dan signifikan penguasaan materi mata kuliah Belajar & Pembelajaran 2, Evaluasi Pengajaran dan praktik PPL secara bersama-sama terhadap kesiapan menjadi guru.Kata Kunci: Kesiapan Menjadi Guru, Penguasaan Materi Mata Kuliah Dasar Kependidikan. ABSTRACTThe objectives of this research are to investigate: 1) the effect of mastery of the course of Learning and Instruction 2 on the preparedness to be a teacher; 2) the effect of mastery of the course of Instructional Evaluation on the preparedness to be a teacher; 3) the effect of mastery of the course of Field Experience Practice on the preparedness to be a teacher; and 4) the simultaneous effect of mastery of the basic courses of education of Learning and Instruction 2, Instructional Evaluation, and Field Experience Practice on the preparedness to be a teacher. This research used the quantitative correlational research method with the causal-comparative approach with the ex-post facto in nature. The population of the research was all of the students of the Study Program of Economics BKK, Accounting Education, theFaculty of Teacher Training and Education, Sebelas Maret University, Surakarta. The samples of the research were taken by using the purposive sampling technique. The data of the research were gathered through questionnaire with Likert scale. The validity of the instrument was tested by using the correlational formula of Pearson Product Moment, the reliability of the instrument was tested by using Alpha Coefficient formula. The prerequisite tests of analysis consisted of normality test, linearity test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The hypotheses of the research were verified by using the simple regression analysis and the multiple regression analysis. The results of the research are as follows: 1) there is a positive and significant effect of mastery of the course of Learning and Instruction 2 on the preparedness to be a teacher; 2) there is a positive but not significant effect of mastery of the course of Instructional Evaluation on the preparedness to be a teacher; 3) there is a positive and significant effect of mastery of the course of Field Experience Practice on the preparedness to be a teacher; and 4) there is simultaneously positive and significant effect of mastery of the basic courses of education of Learning and Instruction 2, Instructional Evaluation, and Field Experience Practice on the preparedness to be a teacher.Keywords: Preparedness to be a teacher, mastery of the basic courses of education